The Influence of Human Resources Information System (HRIS) Implementation on Work Efficiency in the Human Resources Department and Employee Satisfaction at PT Pos Indonesia Main Branch Balikpapan - Ahmad Ahmad; Rian Ubaidillah (International Journal of Management Science and Information Technology, 2026)
This study investigates the impact of implementing the Human Resources Information System (HRIS) on the operational efficiency of the human resources department and the satisfaction levels of employees at PT Pos Indonesia Main Branch Balikpapan. The HRIS serves essential functions such as tracking attendance, processing leave requests, updating employee information, conducting performance evaluations, and facilitating internal communication. Utilizing a quantitative methodology, the research surveyed 120 employees who actively engage with HRIS services. Data analysis was performed through descriptive statistics and multiple linear regression techniques. Findings reveal a positive correlation between HRIS utilization and both work efficiency and employee satisfaction. Specifically, the R² value of 0.428 indicates that HRIS accounts for a significant portion of the variability in work efficiency, while the R² value of 0.396 reflects its influence on employee satisfaction. These results underscore the role of HRIS in streamlining administrative processes, minimizing errors, and enhancing information accessibility. Despite these favorable outcomes, it remains crucial for the organization to invest in user training, ongoing support, and system maintenance to maximize the advantages of HRIS across the board.